In Vitro Activity of Structurally Diverse Nucleoside Analogs against Human Immunodeficiency Virus Type 1 with the K65R Mutation in Reverse Transcriptase - Parikh, Urvi M. (American Society for Microbiology, 2005)
Human immunodeficiency virus type 1 (HIV-1) with a lysine-to-arginine substitution at codon 65 (HIV-1(65R)) of reverse transcriptase (RT) can rapidly emerge in patients being treated with specific combinations of nucleoside analog RT inhibitors (NRTIs). A better understanding of the activity of approved and investigational NRTIs against HIV-1(65R) is needed to select optimal therapy for patients infected with this mutant and to devise strategies to prevent its emergence. Therefore, we tested a broad panel of NRTIs that differed by enantiomer, pseudosugar, and base component against HIV-1(65R) to determine how NRTI structure affects activity. Drug susceptibilities of recombinant wild-type (HIV-1(65K)) or mutant HIV-1(65R) were determined using a single-replication-cycle susceptibility assay with P4/R5 cells and/or a multiple-replication-cycle susceptibility assay with MT-2 cells. All d, l, and acyclic NRTIs were significantly less active against HIV-1(65R) than against HIV-1(65K) except for analogs containing a 3′-azido moiety. Pseudosugar structure and base component but not enantiomer influenced NRTI activity against HIV-1(65R). These findings support the inclusion of 3′-azido-3′-deoxythymidine in drug combinations to treat patients having HIV-1(65R) and to prevent its emergence.